2018
DOI: 10.4244/eij-d-18-00762
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of a biodegradable polymer ultra-thin sirolimus-eluting stent versus a durable polymer everolimus-eluting stent in patients with de novo native coronary artery lesions: the meriT-V trial

Abstract: In the treatment of de novo native coronary artery lesions, the biodegradable polymer ultra-thin SES (BioMime) was non-inferior to a durable polymer EES (XIENCE) at nine-month follow-up. Further studies powered for clinical endpoints are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…The primary safety and efficacy trials meriT-1 [18] and meriT-2 [19] and, more recently, the observational post-marketing multisite registry meriT-3 [14] reported low rates of major adverse cardiovascular events (MACEs) and late stent thrombosis. Finally, the randomized meriT-5 trial [20] demonstrated that BM was non-inferior to the XIENCE DES at 9-month follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…The primary safety and efficacy trials meriT-1 [18] and meriT-2 [19] and, more recently, the observational post-marketing multisite registry meriT-3 [14] reported low rates of major adverse cardiovascular events (MACEs) and late stent thrombosis. Finally, the randomized meriT-5 trial [20] demonstrated that BM was non-inferior to the XIENCE DES at 9-month follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…Series of randomized trials have demonstrated the clinical benefit of ultrathin DES in patients with CHD. [25][26][27] Moreover, according to a meta-analysis study, <70 µm ultrathin-strut DESs, including MiStent, improved 1-year clinical outcomes, in comparison with thicker strut DESs. [28] These results proved that the ultrathin strut of MiStent additionally provides beneficial effect for patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lower-than-previously-reported overall TLR rates of 1.0% in the control DP-EES group (where other randomized trials consistently have reported rates of 2%-5% at 12 months using the same definitions), is significantly underpowered and not prespecified to make this comparison reliable. [39][40][41][42][43][44][45] While between-trial differences are difficult to ascertain, one important factor in our study is that a significant proportion of clinical follow-up was performed between January and July 2020 at the peak of the coronavirus disease 2019 (COVID-19) pandemic. Whether possible pandemic-related hospital presentation delays or avoidance contributed to lower-than-expected TLR rates cannot be fully evaluated.…”
Section: Discussionmentioning
confidence: 99%